2022
DOI: 10.3389/fphar.2022.1026219
|View full text |Cite
|
Sign up to set email alerts
|

Processed lateral root of Aconitum carmichaelii Debx.: A review of cardiotonic effects and cardiotoxicity on molecular mechanisms

Abstract: Fuzi, the lateral root of A. carmichaelii Debx., is a typical traditional herbal medicine with both poisonousness and effectiveness, and often used in the treatment of heart failure and other heart diseases. In this review, we searched domestic and foreign literature to sort out the molecular mechanisms of cardiotonic and cardiotoxicity of Fuzi, also including its components. The major bioactive components of Fuzi for cardiotonic are total alkaloids, polysaccharide and the water-soluble alkaloids, with specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 122 publications
0
6
0
Order By: Relevance
“…Fuzi can be used in the treatment of CVD especially in HF, due to its valuable cardiotonic effect which helps improve heart function and enhance the contractility of the heart muscle ( Zhao et al, 2012 ; Zhang J. et al, 2022 ). In addition, Fuzi has been studied for its potential anti-MI effects, including mitigating mitochondrial dysfunction caused by MI and restoring energy metabolism in the heart ( Wu H. et al, 2019 ).…”
Section: The Potential Impact Of Yyfz On Mitochondria-er Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fuzi can be used in the treatment of CVD especially in HF, due to its valuable cardiotonic effect which helps improve heart function and enhance the contractility of the heart muscle ( Zhao et al, 2012 ; Zhang J. et al, 2022 ). In addition, Fuzi has been studied for its potential anti-MI effects, including mitigating mitochondrial dysfunction caused by MI and restoring energy metabolism in the heart ( Wu H. et al, 2019 ).…”
Section: The Potential Impact Of Yyfz On Mitochondria-er Interactionsmentioning
confidence: 99%
“…These biological processes protect myocardial tissue. Furthermore, water-soluble alkaloids in Fuzi also modulate mitochondria-mediated pathways to promote mitochondrial energy metabolism ( Zhang J. et al, 2022 ).…”
Section: The Potential Impact Of Yyfz On Mitochondria-er Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the mechanism of action, lappaconitine 1 , its major metabolite N -deacetyllappaconitine 2 , and some other alkaloids of Aconitum sp. were found to act as sodium channel blockers [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. It was shown that voltage-dependent Na + channel blockers possesses antinociceptive activity and neuronal activity [ 12 , 15 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…side effects of FZ seriously affect its clinical use (Huang et al, 2018;Yang et al, 2018;Zhang et al, 2022). Processing is an important method to reduce the toxicity of toxic Chinese medicines, and FZ is generally processed before being used in medicines (Xin et al, 2024;Zhang et al, 2021).…”
mentioning
confidence: 99%